Creative activities in chemistry and students' higher order thinking skills - Ramirez, Rachel Patricia B. (2007)
This study was conducted to find out the effect of instruction with creative activities on high school chemistry students' higher order thinking skills. Standard creative techniques as well as strategies developed by the researcher were incorporated into a total of fourteen lessons used in the intervention called Instruction with Creative Activities (ICA). The pretest-posttest control group design was applied in the quasi-experimental study. The sample consisted of 60 third year high school students enrolled in the Regional Science High School in Tumauini, Isabela. One group was exposed to Instruction with Creative Activities, while the other was taught using the Instruction with No Creative Activities. Instruction with Creative Activities had no significant effect on students' higher order learning skills, but it could improve students' skills in evaluating and creating.